Risk perception and transmission potential of Neospora caninum at the wildlife and livestock interface in Minnesota - Minicucci, Larissa A.; Carstensen, Michelle; Cornicelli, Louis; Elmore, Stacey A.; Dubey, Jitender P.; Wolf, Paul; Hildebrand, Erik; Tunseth, Devin (Frontiers in Veterinary Science, 2025)
Neosporosis is a major cause of abortion in cattle with significant economic consequences for infected farms. We collected sympatric human dimensions, livestock, and wildlife data in a pilot study to assess the understanding and significance of Neospora caninum on Minnesota cattle farms and address the biases of producers who often implicate wolves (Canis lupus) for exposing cattle to this parasite. We surveyed veterinarians and producers to assess their knowledge and attitudes regarding N. caninum. We also conducted on-farm risk assessments and estimated N. caninum seroprevalence in domestic and wild animals. Our survey work showed that producers lack an understanding regarding neosporosis and an overall gap in communication exists between veterinarians and their clients relative to risks associated with Neospora. Overall seroprevalence for N. caninum on 10 farms (7 beef, 3 dairy) was 20.9% (n = 450 cattle tested), with individual herd seroprevalence ranging from 0 to 51.3% (median = 9.1%; mean = 16.4%, std. = 19.0%). We found no difference in seroprevalence of N. caninum between farms within and outside of wolf range. Seroprevalence among domestic canid samples was 64.3% (9/14) and among felid samples was 25% (5/20); most farms had at least one seropositive dog and cat. Most farms (90%) had at least one wildlife species test seropositive for N. caninum. On farm risk assessments, combined with serological data, provided strong evidence that domestic dogs present the greatest risk for exposure of N. caninum to cattle. Enhanced communication between veterinarians and producers can foster better outcomes by proactively reducing risk of disease transmission and accepting their role in the outcomes.